Mobile World Past, Present and Future - Hamill, Lynne; Lasen, Amparo (Computer Supported Cooperative Work, 2005)
Why have mobile phones so quickly become part of our everyday lives? This book brings together the perspectives of key researchers in the area to explore lessons on social shaping, examining what can be learnt from the adoption of mobile devices that can be applied to other, newer, digital technologies. Forecasting the impact of new technology is always difficult. Occasionally demand is underestimated, but more often it is overestimated, and at great cost. Digital technology is unlike anything that has gone before, making it particularly difficult to understand its implications for businesses, public services and society in general. By looking at what has happened in the past and what is happening now, and offering methods of using this knowledge to look forward, this book will contribute to reducing expensive forecasting errors in the future. Key reading for all those involved with the future of mobile communications, this book is a valuable resource, particularly for advanced undergraduate and postgraduate students on Mobile Technology courses, practitioners, and researchers working in mobile communications, CSCW and HCI. This volume is a sequel to Brown et al: Wireless World: Social and Interactional Aspects of the Mobile Age, also in the CSCW series. "This book presents a rich insight into how and why the mobile has become so important in today's society. It explores the strong emotional attachment that people have to these devices, and argues that it is people and not the technology that developers must put at the heart of future mobile offerings. A valuable book for industry and academics alike." Dr Phil Gosset, Vodafone Group R&D.